Analisis Kinerja Keuangan Dengan Menggunakan Rasio-Rasio Keuangan Dan Economic Value Added (Studi Kasus: PT. Bank Syariah Mandiri) - Endri Piliang; Abdul Wakil (Tazkia Islamic Finance and Business Review, 2008)
This paper analyzes the financial peformance of Bank Syariah Mandiri (BSM) using financial ratios and Economic Value Added (EVA) method. The ratio of Net Profit Margin (NPM), Return on Asset (ROA), Return on Equity (ROE), and Capital Adequacy Ratio (CAR) show fluctuative result. However, on average, during 2003-2006 financial performance of BSM was increased considerably. While using EVA method, its result during 2003-2006 tend to decreased and even negative. The best performance was happening in 2003, whereby during 2004 - 2006 EVA result was lower than zero meaning that financial performance of BSM do not have any economic contribution to the institution especially for the interest of investor.Keywords: Economic Value Added, NPM, ROA, ROE, CAR